Pengolahan Buah Kelapa Sawit Menjadi Crude Palm Oil (CPO) untuk Meningkatkan Nilai Tambah Pada Tefa Pembibitan Politeknik Negeri Jember - Irma Harlianingtyas; Sugiyarto Sugiyarto; Descha Giatri Cahyaningrum; Dian Hartatie; Ni Nengah Putri Adnyani (Indonesian Journal Publisher, 2025)
The Teaching Factory Nursery at Politeknik Negeri Jember has palm oil plantation which is used for student practice. Oil palm plants have entered the TM (Producing Plant) phase, but the palm fruit produced has never been used. Palm fruit that is not harvested and is ripe, if it falls to the ground, will germinate and grow into a new plant, this will make handling more difficult because you have to uproot the plant to clean it. Another problem is that there are no tools that support the processing of palm fruit into Cruda Plam Oil (CPO). Seeing the huge potential of this palm fruit, the proposing team together with the management of the Teaching Factory Nursery agreed to take advantage of the opportunity through community service activities to produce CPO which will later become red palm oil ready for consumption using simple processing equipment. The service activity begins with a FGD to agree on product manufacture, location and equipment maintenance, as well as product marketing. The proposing team also provides assistance in product creation, storage, packaging, and product marketing for program sustainability. The results of the activity show an increase in partners' knowledge and skills regarding post-harvest management of palm oil. The partners' enthusiasm in demonstrating the stages of processing palm oil into CPO is also able to solve problems and solutions and increase income from product sales.